The Relationship Between Teachers' Classroom English Proficiency and Their Teaching Self-Efficacy in an English Medium Instruction Context - Wang, Changmi (Frontiers in Psychology, 2021)
This article examines the relationship between English medium instruction (EMI) teachers’ classroom English proficiency and their teaching self-efficacy. The literature review highlights the difference between general language proficiency and classroom language proficiency by focusing on the EMI teachers’ language of instruction and their language of interaction. Self-reported data were obtained using two measuring scales from 188 EMI teachers from a Chinese public university. The Pearson correlational analysis indicated that there was a strong positive relationship between the EMI teachers’ classroom English proficiency and their teaching self-efficacy. Among the four constructs of the Classroom English Proficiency Scale, both language of instruction and language of interaction have a higher correlation with teaching self-efficacy than grammar or pronunciation. The linear regression analysis suggests that language of instruction has a significant contribution to the variance of teaching self-efficacy. The findings reveal the need to prioritize the strategic training of language of instruction skills to EMI teachers who are not so proficient in English. Arguably, this helps to foster the achievement and maintenance of higher teacher self-efficacy.